Subepicardial adipose genes contribute to the deterioration of heart failure preserved ejection fraction - Ruiying Zhang; Ruiying Zhang; Ruiying Zhang; Man Wang; Man Wang; Man Wang; Yuheng Lang; Yuheng Lang; Jiaqi Zhang; Jiaqi Zhang; Jiaqi Zhang; Yuchao Wang; et al. (Frontiers in Cardiovascular Medicine)
BackgroundThe mortality of patients with acute myocardial infarction (MI) raised rapidly in last decade and obesity are becoming the major cause to CAD progression, thus inducing heart failure preserved ejection fraction (HFpEF). However, why visceral adipocytes show different effects on healthy and ageing cardiomyocytes is less known.MethodsGSE251971 was downloaded and Venn diagram between visceral adipocyte genes genes and DEGs was performed to obtain visceral adipocyte-associated DEGs in heart failure. Protein-protein interaction (PPI) network was constructed to obtain the hub genes utilizing the Cytoscape plugin Cytohubba. The hub genes and their interactions were analyzed using NetworkAnalyst 3.0 and for validation, the hub genes expressions were analyzed using Single-cell sequencing data, cell lines and human sub-epicardial tissues and blood samples.ResultsUsing Venn diagram, 71 visceral adipocyte-associated DEGs were identified. Nine hub genes were obtained, including OGN, SELL, FOS, NKG7, LOX, HBB, CXCL9, CP and ALOX5. Single-cell sequencing demonstrated all hub genes were highly expressed in human hypertrophic cardiomyopathy and ischemic cardiomyopathy patients with end-stage heart failure. The related OGN, FOS, NKG7 and ALOX5 mRNA expressions were significantly highly expressed in sub-epicardial tissues in HFpEF patients. AUCs of OGN, FOS and ALOX5 were 0.902, 0.795 and 0.730, and the AUC of joint ROC of OGN, FOS and ALOX5 was 0.946. Additionally, FOS, ALOX5 and OGN expressions were increased at follow up 1 year recurrence, while decreased at follow up 2 year recurrence. Mechanically, FOS and ALOX5 were highly expressed in macrophages under hypoxia, while OGN was highly expressed in fibroblasts under hypoxia. SASPs, including IL1α, IL1β, IL6 and TNFα, decreased in hypoxic macrophages after FOS and ALOX5 knockdown or both. Also, SASPs decreased in hypoxic fibroblasts after OGN knockdown. These results suggested that FOS, ALOX5 and OGN may affect cell senescence after hypoxia, thus inducing myocardial infarction and HFpEF progression.ConclusionThe screened hub genes, including OGN, FOS and ALOX5, were validated using single-cell sequencing data, cell lines and human samples, which can be therapeutic targets for the treatment to cell senescence under hypoxia and prediction to heart failure progression to HFpEF.